Collaboration Strategy By Design To Achieve Slum Area Reduction Target: Case Study Of Kotaku Program Kepulauan Riau Province 2018-2022 - Efendi H. Pangondo; Muhammad Juang Putra; Burhanudin Burhanudin; Hamsani Hamsani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This paper presents a model of collaboration strategy